(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The constitution of India dreams of a healthy society, and in furtherance of it has granted many rights to children. Chapters on fundamental rights and Directive principles laid down detailed provisions, such as basic survival rights of life, development rights as regard to education, religion, cultural and freedom of thought, conscience and also protection rights from several kinds of abuses and exploitation. The Juvenile Justice System is the most active and illuminating framework espoused by people around the world with regard to children’s whole development. Its primary goal is to reform the degenerates and to protect the vulnerable infants. A youngster should be rehabilitated and reintegrated into the family as soon as possible. In India, a comprehensive legal framework for dealing with children in conflict with the law and children in need of care and protection has been established. The aim of this paper, thus, is to critically analyze this legal framework with special focus on Jammu and Kashmir. The larger question that will be investigated is how successful Juvenile Justice Boards and Child Welfare Committees have been in ensuring justice to the children.